DISTRIBUTION OF FRESHWATER SNAILS WITH SPECIAL REFERENCE TO SCHISTOSOMIASIS INTERMEDIATE HOST IN EL-GENAID SUGAR CANE FARM, CENTRAL SUDAN - Gasmelseed, Nagla; Babiker, Ahmed (Gezira Journal of Health Sciences; Vol 4 No 1 (2008), 2008)
Several sugar cane factories for production of sugar in the Sudan. To each of these factories, a sugar cane farm was attached. Snail distribution, and specially distribution of the intermediate host snails of schistosomiasis, in the cane farms, in the Sudan, was never studied. The study was carried out from February 1995 to May 1996. The objectives is to study on the distribution of fresh water snails in a sugar cane farm in the Sudan,To determine the distribution of the different species seasonally in the canalization system of the sugar cane farm, with special reference to schistosomiasis intermediate host snails. Twenty scoops were taken at each sampling site during the monthly visits. Snails were identified to the species level intermediate host snails were screened for patent infection. The canalization system farm is a suitable habitat for fresh water snails. Seven species of snails are found in the canals. The prosobranchs snails, Cleopatra and Melanoides, dominate all other species. Snail species show marked variation between the canals and in the monthly distribution.  The density of all snail species drops during the rainy season. Environmental factors; such as water flow, water level and density of vegetation; do no effect the distribution of the fresh water snails in the canalization system.  The reproduction of B. pfeifferi snails in Algenaid farm has been affected by unknown factors which need further investigation to determine the reasons. There is the possibility of a shift from S. mansoni to S. haematobium.